Physiotherapy Management in Cardiac Rehabilitation Phase-I - Munaza Tabassum, Amna Shahid, Wajeeha Zia, Muhammad Umer Arshad (Pakistan Journal of Medical & Health Sciences, 2022)
Cardiac diseases are the considered one of the prevalent disease in community nowadays. It involves myocardial infarction, coronary artery disease, valvular disease. Patients suffering from these conditions have taken the surgical treatment. Surgical procedures are common among all the patients and coronary graft bypass surgery to reduce the complications and symptoms such as dyspnea, chest pain, and fatigue is frequently used procedure. These procedures leads towards the post-operative complications and recovery depends upon the early ambulation and physical activity. Physiotherapy is need of the time to improve the symptoms and quality if life of these patients. Multiple techniques of physiotherapy are beneficial and necessary in cardiac rehabilitation phase-I.